2002
DOI: 10.1108/00035590210413557
|View full text |Cite
|
Sign up to set email alerts
|

The influence of the cement paste microstructure on corrosion and the adherence of reinforcing bars as a function of the water–cement ratio

Abstract: Hardened cement paste is a heterogeneous system resulting from the grouping of particles, films, microcrystals and other solid structural elements bounded in a porous mass. The cement paste microstructure must be understood firstly due to its influence on concrete properties. The behaviour of concrete greatly depends on the conformation of localised special structures rather than on general structures found in the mass cement paste. The objective of this paper was to study the cement paste microstructure, as a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
0
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 6 publications
4
0
0
Order By: Relevance
“…Rebars extracted from N1 specimens, stored in tap water, presented two well differentiated regions after SEM examination. The most widespread morphology was constituted by gels with filament like formations (Figure 6(a)) and was similar to others reported in the literature (Romagnoli et al , 2002). Spectral data showed that these formations were rich in hydraulic compounds (SiO 2 : 20‐25 per cent; CaO: 32‐40 per cent) with lower amounts of iron oxides (Fe 2 O 3 : 11‐19 per cent) and carbon dioxide (CO 2 : 8‐10 per cent).…”
Section: Resultssupporting
confidence: 88%
See 2 more Smart Citations
“…Rebars extracted from N1 specimens, stored in tap water, presented two well differentiated regions after SEM examination. The most widespread morphology was constituted by gels with filament like formations (Figure 6(a)) and was similar to others reported in the literature (Romagnoli et al , 2002). Spectral data showed that these formations were rich in hydraulic compounds (SiO 2 : 20‐25 per cent; CaO: 32‐40 per cent) with lower amounts of iron oxides (Fe 2 O 3 : 11‐19 per cent) and carbon dioxide (CO 2 : 8‐10 per cent).…”
Section: Resultssupporting
confidence: 88%
“…The carbon dioxide content was a little higher than in samples cured in the air (CO 2 : ∼23‐33 per cent). Three different morphologies were observed in FC specimens: a cracked surface constituted by amorphous plates (Figure 9(a)), formations similar to those reported for OCP hydration products (Romagnoli et al , 2002) in certain zones of the rebars (Figure 9(b)) and, finally, the third one with high calcium oxide content and low levels of iron oxide (Figure 9(c)). All the formations were enriched in hydraulic compounds as it was revealed by the higher contents of SiO 2 and CaO.…”
Section: Resultssupporting
confidence: 60%
See 1 more Smart Citation
“…Rebars extracted from specimens elaborated with OPC, stored in tap water, presented two well differentiated regions after SEM examination. The most widespread morphology was constituted by gels with filament-like formations (Figure a) and was similar to others reported in the literature. Spectral data showed that these formations were rich in hydraulic compounds (SiO 2 : 20−25%; CaO: 32−40%) with lower amounts of iron oxides (Fe 2 O 3 : 11−19%) and carbon dioxide (CO 2 : 8−10%). The other morphology contained gels constituted by nonexpansive iron oxihydroxides (Figure b).…”
Section: Resultssupporting
confidence: 84%